Personal Hygiene dan Sanitasi Lingkungan pada Pengelolaan Makanan di Masa Pandemi Covid-19 di Tempat Makan â€œAyam Penyetâ€ Kelurahan Air Dingin, Kecamatan Bukit Raya - Hayana Hayana; Winda Septiani; Hetty Ismainar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Coronavirus (Covid-19) is a non-segmented single-stranded positive RNA virus. the Coronaviridae family, and the subfamily Orthocoronavirinae. Hygiene is health efforts by caring for and protecting the subject.. Positive cases of Covid-19 currently reach 63,360,234 million people worldwide with a total of 1,475,825 million deaths, Pekanbaru City has a total of 9,886 thousand cases of Covid-19 . the researcher took the research location in two places in Air Cold sub-district, these two locations have places to eat and quite a lot of buyers because this area is the location where students live and where students buy food, a place to relax and enjoy food with friends, and this location is in the UIR campus area which has a lot of visitors. This study aims to see how far the application of food management hygiene and sanitation has been applied during the Covid-19 pandemic. This type of research is Qualitative Analysis using the Case Survey method and conducting observations and in-depth interviews. There were 12 informants in this study with 4 key informants as owners of the Ayam Penyet restaurant in Bukit Raya District, 4 main informants, namely employees of the Ayam Penyet restaurant, and 4 supporting informants, namely visitors. This research was conducted in January-July 2022. The results showed that there were several stages that did not meet the requirements based on KepMenkes RI No 942/MENKES/SK/VII/2003, including the stages of managing hygiene conditions, equipment sanitation, food storage, processing conditions food, food storage, food serving process and what meets the requirements is the condition of clean water. It is hoped that the two places to eat will maintain more hygiene and sanitation when handling food and during the Covid 19 period they should use health protocols such as using masks and glovesi.